Electrophysiology study in patients with supraventricular tachycardia (Texas Journal of Medical Science, 2023)
Supraventricular tachycardias are paroxysmal tachyarrhythmias which require atrial or atrioventricular nodal tissue or both for their initiation and maintenance & they are often recurrent, occasionally persistent, and a frequent cause of visits to emergency rooms and primary care physicians.